2009
DOI: 10.1103/physrevlett.102.017006
|View full text |Cite
|
Sign up to set email alerts
|

Hot Spots and Waves inBi2Sr2CaCu2O8Intrinsic Josephson Junction Stacks: A Study by Low Temperature Scanning Laser Microscopy

Abstract: Recently, it has been shown that large stacks of intrinsic Josephson junctions in Bi2Sr2CaCu2O8 emit synchronous THz radiation, the synchronization presumably triggered by a cavity resonance. To investigate this effect we use low temperature scanning laser microscopy to image electric field distributions. We verify the appearance of cavity modes at low bias and in the high input-power regime we find that standing-wave patterns are created through interactions with a hot spot, possibly pointing to a new mode of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
205
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(225 citation statements)
references
References 34 publications
14
205
6
Order By: Relevance
“…The appearance of such hot spots whose positions are asymmetric with respect to the center of the mesas have been already reported in previous experimental studies. [20][21][22] …”
Section: Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of such hot spots whose positions are asymmetric with respect to the center of the mesas have been already reported in previous experimental studies. [20][21][22] …”
Section: Calculation Methodsmentioning
confidence: 99%
“…Moreover, the radiation patterns emitted by inhomogeneous samples have not been investigated in previous studies. Recently, Wang et al have reported the appearance of hot spots where the temperature is locally high, [20][21][22] and these inhomogeneities are considered to affect the emission from the IJJs.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in the plot, the IV-characteristics are strongly influenced by self-heating, to the extent that it is S-shaped, which is typical for mesas of this size [12,15]. For the mesas on this chip, THz emission occurs where dI/dV is very large, or even negative, and it has been suggested [16] that this may be essential for some modes of THz emission in these devices. The jumps in the IV-curves around 40 mA may be a signature of the formation of hot-spots in the mesas [16].…”
mentioning
confidence: 89%
“…For the mesas on this chip, THz emission occurs where dI/dV is very large, or even negative, and it has been suggested [16] that this may be essential for some modes of THz emission in these devices. The jumps in the IV-curves around 40 mA may be a signature of the formation of hot-spots in the mesas [16]. The over-all features of the IV-curves of different mesas are very similar; however, details vary which will affect their synchronization.…”
mentioning
confidence: 99%
“…While Shapiro-steps have remained a tool in exploring new directions in Josephson physics, for instance in atomic point contacts [2][3][4][5][6] , other nonlinear phenomena, like synchronization, have been investigated in arrays of JJs: as a test-bed for generic theory models to capture synchronization phenomena 7,8 , but as importantly with the prospect of applications as sources of more intense coherent radiation 9 , cf. also new developments using intrinsic arrays [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%